Individualized initiation of statin therapy determined by baseline LDL-C: Are you more likely to achieve goal LDL-C? - James R Clem; Joe D Strain; Debra K Farver (Dove Medical Press, 2009)
James R Clem1, Joe D Strain2, Debra K Farver31South Dakota State University College of Pharmacy Sioux Falls, South Dakota, USA; 2South Dakota State University College of Pharmacy, Rapid City Regional Hospital, Rapid City, South Dakota, USA; 3South Dakota State University College of Pharmacy, Yankton, South Dakota, USAAbstract: Cardiovascular disease remains the leading cause of death in the world. A significant amount of clinical data are available to demonstrate the positive influence that 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor (statin) therapy has on slowing the progression of cardiovascular disease and improving clinical outcomes. Achieving the treatment goals for cholesterol in cardiovascular disease continues to present challenges. Recent clinical trial information is available assessing the use of more aggressive initial doses of statin therapy based on initial low-density lipoprotein cholesterol (LDL-C) measurements in an attempt to reach treatment goals sooner. Six clinical trials assessed low-, moderate- and high-risk individuals as well as those with type 2 diabetes mellitus to determine if this treatment approach is both safe and effective. The studies concluded that initial dosing of statin therapy determined by a baseline LDL-C measurement demonstrates good achievement in reaching treatment goals and does not result in a higher rate of adverse effects.Keywords: LDL-C, statin therapy, treatment goals